CO2 hydrogenation by phosphorus–nitrogen PN3P-pincer iridium hydride complexes: elucidation of the deactivation pathway. Issue 34 (12th August 2019) - Pan, Yupeng; Guan, Chao; Li, Huaifeng; Chakraborty, Priyanka; Zhou, Chunhui; Huang, Kuo-Wei
Abstract : PN 3 P–Ir pincer hydride complexes were synthesized and characterized as catalysts and key intermediates in the direct hydrogenation of CO2 to formate under mild conditions. Abstract : PN 3 P–Ir pincer hydride complexes were synthesized and characterized as catalysts and key intermediates in the direct hydrogenation of CO2 to formate under mild conditions. The formation of a dearomatized PN 3 P*–Ir(i )–CO species was identified as a plausible key process accountable for the loss of catalytic activity in the CO2 hydrogenation.